Content validation of the Tilburg Frailty Indicator from the perspective of frail elderly. A qualitative explorative study. Issue 3 (November 2015) - Andreasen, Jane; Lund, Hans; Aadahl, Mette; Gobbens, Robbert J.J.; Sorensen, Erik E.
Highlights The Tilburg Frailty Indicator (TFI) measures frailty in the bio-psycho-social domains. A deductive content analysis validated TFI from a target population perspective. The TFI reflects the issues that frail elderly themselves experience as troublesome. However, important issues from a target population perspective were not covered. A valid screening tool for frailty is important for clinical practice.